A autonomia desportiva na Constituição da República de 1988 - Accioly, Caroline Nogueira (2016)
After the 1988 Constitution sports received a more prominent place in our society, through its inclusion as a chapter in our Lex Mater. This innovation created the backbone of our sports system: the principle of autonomy of sport. The purpose of this study is to characterize, understand and delimit it so that its applicability is neither overlooked or enlarged, providing the necessary protection to the Sports Law and for its continued development in our country